KARAKTERISTIK FISIKOKIMIA DAN PROFIL SENSORI MANGGA GEDONG PADA DUA TINGKAT KEMATANGAN - Mutiara Utami; Christofora Hanny Wijaya; Darda Efendi; Dede Robiatul Adawiyah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Mangoes of Gedong variety (Mangifera indica L. var. gedong) is one of the exported commodities from Indonesia. Half mature mangoes of this type are called gedong mangoes, whereas the full ripe mangoes are called gedong gincu mango. This research aimed to determine the physicochemical charac-teristics, sensory attributes and volatile compounds of the above two mango types. The results showed that gedong mangoes had a lower pH value, less total soluble solid, harder texture, and the skin color had a lower intensity of lightness, redness, and yellowness as compared to gedong gincu mango. The sensory analysis using rate-all-that-apply (RATA) method showed that attributes of color, fibrous, aroma (fruity, caramel, cooked, green, fermented, floral, sweet), taste (sweet, sour), melting, firmness, juiciness and astringency were significantly different between gedong and gedong gincu mango. The overall sensory of gedong gincu mangoes was more preferred by the panelists with the hedonic score of 6.20±0.09 (6= like) while that of gedong mango was 5.37±0.09 (5= slightly like). The sensory profiles of both mangoes were supported by the analysis of their volatile compounds. The gedong mango had predominantly green type of volatiles aroma while the gedong gincu was dominated by the fruity sweet ones. The sensory acceptability of gedong gincu mango was significantly higher rather than that of gedong mango.